2018
DOI: 10.1044/2018_ajslp-17-0030
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Using a Multimodal Approach to Melodic Intonation Therapy

Abstract: Integration of melodic intonation therapy through the addition of musical elements may result in improved speech and expressive language skills when administered over a 9-month period in conjunction with a group socialization program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The prognostic score will display more positive results. In the case report by Slavin and Fabus (2018), the therapist trained in NMT who performed MIT treatment also showed positive results. Although the samples in the above studies are generally small, the results are similar to the RCT study of more than 15 people, and the intervention process tends to be more musical.…”
Section: Case Studies and Small Sample Studies Have The Characteristics Of Complete Specific Treatment Interventionsmentioning
confidence: 92%
See 1 more Smart Citation
“…The prognostic score will display more positive results. In the case report by Slavin and Fabus (2018), the therapist trained in NMT who performed MIT treatment also showed positive results. Although the samples in the above studies are generally small, the results are similar to the RCT study of more than 15 people, and the intervention process tends to be more musical.…”
Section: Case Studies and Small Sample Studies Have The Characteristics Of Complete Specific Treatment Interventionsmentioning
confidence: 92%
“…Seven scores were improved in Amsterdam Nijmegen Everyday Language Test (ANELT); 22.5 scores were improved in Sabadel Story Retell Task. Slavin and Fabus (2018) conducted a before-after MIT intervention in a 63year-old man with chronic aphasia for 10 years. Unlike other studies, Slavin teamed up with a professional music therapist to intervene.…”
Section: Case Studiesmentioning
confidence: 99%
“…Initially, this patient was offered SLT and a modified MIT procedure. Registering that a 9-month MIT combined with musical components and coupled with group treatment may result in augmented speech and motor language abilities [82]. Further, there is assuring testimony that adjustments to home-based applications, such as aphasia-favorable written guidance and music, promote proper home training [83].…”
Section: Music-based Therapymentioning
confidence: 99%
“…MIT has been regarded as one of the most promising therapies for patients with non-fluent aphasia in that it could promote motor speech control. For many years, a number of studies in MIT have been carried out and reported improvements in the patients' connected speech [9][10][11]. The role of "melodic" elements, in particular, has been studied in depth [12][13][14], with the widely held belief that the rhythmic component of intoned-speech production is essential for the facilitation of patients' speech output, whereas the contribution of pitch settings to MIT's overall efficacy has been a source of contention [14].…”
Section: Introductionmentioning
confidence: 99%